Decoupling the Effects of Self‐Assembled Monolayers on Gold, Silver, and Copper Organic Transistor Contacts. Issue 2 (22nd December 2014) - Kim, Chang‐Hyun; Hlaing, Htay; Hong, Jong‐Am; Kim, Ji‐Hoon; Park, Yongsup; Payne, Marcia M.; Anthony, John E.; Bonnassieux, Yvan; Horowitz, Gilles; Kymissis, Ioannis
<x xml:space="preserve">Abstract</x> In bottom‐contact organic field‐effect transistors (OFETs), the functionalization of source/drain electrodes leads to a tailored surface chemistry for film growth and controlled interface energetics for charge injection. This report describes a comprehensive investigation into separating and correlating the energetic and morphological effects of a self‐assembled monolayers (SAMs) treatment on Au, Ag, and Cu electrodes. Fluorinated 5, 11‐bis(triethylsilylethynyl) anthradithiophene (diF‐TES‐ADT) and pentafluorobenzenethiol (PFBT) are employed as a soluble small‐molecule semiconductor and a SAM material, respectively. Upon SAM modification, the Cu electrode devices benefit from a particularly dramatic performance improvement, closely approaching the performance of OFETs with PFBT‐Au and PFBT‐Ag. Ultraviolet photoemission spectroscopy, polarized optical microscopy, grazing‐incidence wide‐angle X‐ray scattering elucidate the metal work function change and templated crystal growth with high crystallinity resulting from SAMs. The transmission‐line method separates the channel and contact properties from the measured OFET current–voltage data, which conclusively describes the impact of the SAMs on charge injection and transport behavior.